2019
DOI: 10.1016/j.ajo.2018.09.014
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based, Case-Control Evaluation of the Association Between Hormonal Contraceptives and Idiopathic Intracranial Hypertension

Abstract: Purpose To determine if the use of oral contraceptive pills (OCP) and other hormonal contraceptives are associated with a higher incidence of idiopathic intracranial hypertension (IIH). Design Retrospective, population-based, case-control study Methods Setting Female IIH patients evaluated between January 1, 1990 and December 31, 2016 were identified using the Rochester Epidemiology Project (REP), a record-linkage system of medical records for all patient-physician encounters among Olmsted County, Minnesot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 36 publications
4
21
0
Order By: Relevance
“…the exposure to hormonal contraceptives was lower in IIH than in GP controls. This supports previous reports that use of contraceptives containing oestrogen is not a risk factor for IIH development (4,6,8) and is in line with the results from Kilgore et al (9). However, we cannot rule out that there might be an increased risk with certain types of hormonal contraceptives (11).…”
Section: Factors Associated With Iihsupporting
confidence: 93%
See 1 more Smart Citation
“…the exposure to hormonal contraceptives was lower in IIH than in GP controls. This supports previous reports that use of contraceptives containing oestrogen is not a risk factor for IIH development (4,6,8) and is in line with the results from Kilgore et al (9). However, we cannot rule out that there might be an increased risk with certain types of hormonal contraceptives (11).…”
Section: Factors Associated With Iihsupporting
confidence: 93%
“…For some of these factors, the strength of the association has been questioned (4). There are few previous case-control studies available with a representative control population investigating risk factors associated with IIH, most including between 20-60 cases (5)(6)(7)(8)(9) aside from two studies investigating fluoroquinolones antibiotics (339 cases) (10) and hormonal contraceptives (3323 cases) (11). Otherwise knowledge on risk factors is based primarily on case reports or reviews (4,12).…”
Section: Introductionmentioning
confidence: 99%
“…10,14 Despite similar risk factors and age-group, female preponderance was found among IIH patients in the study of Bruce et al 15 Hormonal etiology could be a predisposing factor for IIH in the female during the fertility period. Previous studies had shown an association of OCP and IIH which was not found to be related in a recent study by Kilgore et al 16 Headache characteristics in IIH are nonspecific. Usually early symptoms are similar to tension-type headaches or migraine.…”
Section: Resultsmentioning
confidence: 76%
“…While a previous case series reported OCP use in 24% of IIH patients, 27 a case-control study comparing patients with IIH to age, sex and body mass index-matched patients did not find a significant association between OCP use and IIH. 42 Headache was the most commonly reported symptom. Consistent with prior literature, we have identified the co-occurrence of IIH and either pre-existing or subsequent headache diagnoses, in particular, migraine.…”
Section: Discussionmentioning
confidence: 99%